CONTRALORÍA GENERAL DE LA REPÚBLICA DEL PERÚ – EN EL DERECHO CONSTITUCIONAL - CUBA MUJICA, NILO (2020)
In this research work on the subject of the Comptroller General of the Republic, which is an autonomous constitutional body of the Peruvian state, being the highest authority of the National Control System. We will talk about the different general functions of the Office of the Comptroller General of the Republic, its legal powers that are based on the Organic Law - Law No. 27785 and constitutional that is based on the 1993 Constitution. It is understood that the comptroller is the governing body of the national control system and from there derives the power that it has to order the public entities to carry out the internal audits and audits they deem necessary. For example, if an official acknowledges a minor offense and wants to disclaim his responsibility, he can go to the comptroller's own motive and, in turn, order the entity to carry out internal control. The comptroller has the attribution of carrying out directly, the external external control over the acts of the entities. You can do it as part of your operations or as a result of a complaint, whether a private person, an official who wants to welcome effective collaboration or a congressman from the republic. Keywords: Comptroller, constitutional, law.